Group Model Building Using Systems Dynamics to Achieve Enduring Agreement - Scott, Rodney (SpringerBriefs in Operations Research,, 2018)
This book describes the cognitive and interpersonal effects of group model building, and presents empirical research on what group model building achieves and how. Further, it proposes an integrated causal mechanism for the effects on participants. There have been multiple previous attempts at explaining the effects of group model building on participants, and this book integrates these various theories for the first time. The causal mechanisms described here suggest a variety of design elements that should be included in group model building practice. For example, practitioners typically try to reduce complexity for clients, to make the process feel more accessible. In contrast, the findings presented here suggest that the very act of muddling through complexity increases participants' affective commitment to the group and the decisions made. The book also describes implications for theory and practice. System dynamics has traditionally been interested in using technical modeling processes to make policy recommendations. Group model building demonstrates that these same techniques also have implications for group decision making as a method for negotiating agreement. The book argues for the value of group model building as a mediating or negotiating tool, rather than merely a positivist tool for technical problems.